Swallowing Outcomes in Dysphagia in Children with Spinal Muscular Atrophy: Protocol for a scoping review - (:unkn) unknown (My University, 2024)
Background: Spinal Muscular Atrophy (SMA) is a genetic neuromotor disease characterized by muscle weakness and atrophy. Among the clinical manifestations, swallowing difficulties can be associated with this disease and have a significant impact on pulmonary health, malnourishment, and aspi- ration pneumonia. Swallowing-related outcomes se- lected for measurements differ from protocol to protocol in clinical re- search studies, which makes it hard to identify commonalities across different studies and apply standardized swallowing interventions. Objective: This research aims to explore the characteristics of swallowing-related outcomes in clinical research in children with SMA to contribute to future research about dysphagia management in this population. Methods: All research studies exploring clinical interventions for swallowing difficulties in children below 18 years of age with dysphagia associated with SMA will be included. Five electronic databases (EMBASE, CINAHL Complete, PubMed, Web of Science, and PsycInfo) will be searched, with no restrictions on dates, language, or type of study. Two independent reviewers will assess articles to meet the following criteria: 1) dysphagia intervention studies in children with SMA; 2) outcomes of dys- phagia intervention; 3) methods of measurement of outcomes; 4) time- points and frequency of measurement. Conclusions: Examining the outcomes of dysphagia intervention in children with SMA will help identify the gaps in the literature and raise awareness about the lack of agreement in the management of swallowing difficulties experienced in this population, laying the foundations for future research to ex- pose outcomes that are neglected.
PUBLISHED
Keywords: Dysphagia, Spinal Muscular Atrophy, Rehabilitative Interventions, Outcomes, Scoping Review; Inclusive Society; DYSPHAGIA; Evidence based practice; Swallowing Disorders; Chronic Health Condition; Physical disability; Children